Pengaruh Program Pemberian Makanan Tambahan (PMT) Berkelanjutan Terhadap Perbaikan Gizi Stunting di Kota Binjai - Manik, DiniLa Putri Olina Br.; Armansyah , Andini septiana; Gulo , Nanda Putri Berlian; Garamba, Indah Purnama Sari; Zai , Lady Angelita; Paninsari , Debora (Journal of Pharmaceutical and Sciences, 2025)
Background: Stunting remains a serious public health problem in Indonesia, including in Binjai City, with a prevalence rate that continues to fluctuate and requires effective intervention. Stunting is caused by chronic malnutrition and results in growth failure. The Supplementary Feeding Program (PMT) is a specific intervention expected to improve the nutritional status of toddlers. Objective: This study aims to analyze the effect of the continuous Supplementary Feeding Program (PMT) on improving the nutritional status of stunted toddlers in Binjai City. Methods: This study used a quasi-experimental design (one-group pretest-posttest). The research population was 44 stunted toddlers registered in the Binjai City Stunting Reduction Acceleration Team (TPPS) program. Data was collected through direct anthropometric measurements (body weight and height) before and after the 90-day PMT intervention. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The results showed a statistically significant improvement in the toddlers' nutritional status after the PMT intervention. This was evidenced by an increase in the indicators of body weight (p < 0.001), height (p < 0.001), W/A index (p = 0.002), H/A index (p < 0.001), and W/H index (p < 0.001). Conclusion: The continuous Supplementary Feeding Program (PMT) was proven effective in improving the nutritional status of stunted toddlers. This program can be used as a reliable strategy in efforts to accelerate the reduction of stunting rates in Binjai City.